CARDIOVASCULAR PATIENT WITH PERMANENT PACEMAKER DUE TO COMPLETE ATRIOVENTRICULAR BLOCK - Oladipo, D. L.; Swanzy-Krah, J.; Pochinska, M. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
Permanent pacemaker implantation and medical therapy due to complete atrioventricular block and comorbid cardiac pathology are considered at an example of clinical case. Permanent pacemaker solved the problem of AV-block, however, drug therapy due to arterial hypertension, heart failure and dyslipidemia is not canceled and requires modification. Permanent pacemaker solved the problem of AV-block, however, drug therapy due to arterial hypertension, heart failure and dyslipidemia is not canceled and requires modification.